Persepsi Pengunjung terhadap Daya Tarik Objek Wisata Mountain Valley di Agrowisata Perkebunan Teh Kecamatan Kabawetan Kabupaten Kepahiang - Sherlya Maydasari; Mira Yanuarti; Anadiya Pingki; Dwita Frisdinawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research was conducted in December 2024 - January 2025. This study aims to: (1). Determine visitor perceptions of the Attractions, Facilities, and Services at the Mountain Valley tourist attraction in the Tea Plantation Agrotourism, Kabawetan District, Kepahiang Regency. (2). Determine the effect of Attractions, Facilities, and Services at the Mountain Valley tourist attraction in the Tea Plantation Agrotourism, Kabawetan District, Kepahiang Regency on tourist visits. The data analysis method used in this study is the descriptive method, multiple linear regression analysis and the T test. In this study, the researcher used a random sampling technique, namely taking samples randomly. The Probability technique is a sampling technique that provides an equal opportunity for each element to be selected as a respondent member. Respondents in this study were measured using the Slovin formula with a tolerance limit of error (10%). Based on the results and discussion, it can be concluded that the perception of visitors to the Mountain Valley Tourism Object in Kabawetan District, Kepahiang Regency, most of the overall chose the category